2017
DOI: 10.1177/0886368718772254
|View full text |Cite
|
Sign up to set email alerts
|

Two Major Antecedents of Salesforce Motivation: Salesforce Control Systems and Compensation Plans

Abstract: Salesforce motivation is important for the success of the organization. Unless and until the salesforce is motivated, the organization will not be able to prosper. There are various factors that are responsible for salesforce motivation. It has been found that out of these many factors, the impact of salesforce control system and salesforce compensation plans is inevitable. Therefore, this study makes an attempt to analyze the impact of these two factors on salesforce motivation by following a review of select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In a study based on a survey of 210 sales managers working in an export firm, the researchers found that the behaviour-based system of control has a significant impact on motivational and attitudinal dimensions of the sales managers . Fatima (2017), in a review-based study, found that the behaviourbased control system has a positive impact on salesforce intrinsic motivation. Miao and Evans (2012) divided behaviour-based control into activity-based and capability-based control and found no significant relationship between intrinsic motivation and behaviour-based control.…”
Section: Intrinsic Motivationmentioning
confidence: 99%
See 3 more Smart Citations
“…In a study based on a survey of 210 sales managers working in an export firm, the researchers found that the behaviour-based system of control has a significant impact on motivational and attitudinal dimensions of the sales managers . Fatima (2017), in a review-based study, found that the behaviourbased control system has a positive impact on salesforce intrinsic motivation. Miao and Evans (2012) divided behaviour-based control into activity-based and capability-based control and found no significant relationship between intrinsic motivation and behaviour-based control.…”
Section: Intrinsic Motivationmentioning
confidence: 99%
“…In a study based on a survey of 210 sales managers working in an export firm, the researchers found that the behaviour-based system of control has a significant impact on motivational and attitudinal dimensions of the sales managers (Theodosiou & Katsikea, 2007). Fatima (2017), in a review-based study, found that the behaviour-based control system has a positive impact on salesforce intrinsic motivation.…”
Section: Salesforce Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, compensation plans must be at least baseline competitive to attract and retain good talent (Kaplan, 2007). Best practices as it relates to compensation are utilized in other professions (e.g., Fatima, 2017; Low, 2016; Roberge, 2015), and school districts can benchmark and learn from other industries to ensure that teachers are paid equitably. Specifically, decision makers may benefit from management practices, including human resource management practices, and use appropriately attractive compensation to aid in more effective recruitment, as well as increased satisfaction, motivation, and retention of teachers.…”
Section: Introductionmentioning
confidence: 99%